Real world applications panel healthcare and medicine - Odewahn, Andrew; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, Calif.) ([United States?] : O'Reilly Media, 2011)
"Information is changing healthcare forever. From the study of epidemics, to machine learning that can improve diagnosis, to the sequencing of the human genome, we're doing the math of life itself. This panel of practitioners will show us what they're doing in healthcare, pharmaceuticals, and genomics, and how it will change the way we discover, treat, and eliminate disease." --Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, CA.
Electronic reproduction.
Keywords: Application software -- Development; Electronic books